Semiotic Study of Football Team Logo in La Liga - I Putu Gede Wiweka (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This study is entitled Semiotic Study of Football Team Logos in La Liga. Each football team has a logo with the historical aspect to show their identity to the public, and where the team was built. Therefore, the public can recognize the team just by looking at the logo. The formulation of the problem in this study is to discuss some of the logos of the club from a semiotic perspective. The aims of this study are to identify and describe the verbal and non-verbal signs used in La Liga team logos, and to analyze the meanings of La Liga team logos based on the color terms. The data sources are six logos of La Liga team. The data in the forms of verbal and visual signs were collected using a documentation method. In order to analyze the verbal and visual signs, as well as the color terms, the qualitative method was applied. The results of the study reveal that the verbal signs on six of La Liga team logos generally shows the acronym of the name of the football club. The non-verbal signs found on six logos are generally in the form of symbols and icons related to football and the kingdom in Spain. The meanings of the logos itself are identified from the colors used in the logo. The most used colors are red, yellow, blue and black. The colors in the logo help the fans understand the meaning and purpose of the logo.